Analisis Konseptual tentang Penerapan Teori Probabilitas Lanjut dalam Pengembangan Model Statistik Modern - Hanggoro, Dimas Banu Dwi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study aims to examine the application of advanced probability theory in the development of modern statistical models through a Systematic Literature Review approach to 25 scientific articles published in 2020–2025. This study is complemented by a bibliometric analysis using VOSviewer to explore the relationship of terms, temporal trends, and concept density in the literature. The visualization results show that the terms